The Right to Die Through the Analysis of the Slovenian Voluntary Assisted Dying Bill - Bračič, Andrej (Medicine, Law & Society, 2025)
This article provides an analysis of the Slovenian Voluntary Assisted Dying Bill, in both its previous and amended versions, which is founded upon the paradigm “My life, my right”. The original bill, which was regarded as highly liberal, contained numerous exceptions that effectively allowed euthanasia for all individuals with chronic illnesses or disabilities. This analysis critically examines the most controversial legal provisions of the bill and anticipates consequences should it be implemented, particularly from the perspective of vulnerable healthcare users. The analysis demonstrates that the original formulation of the right to medically assisted dying conflicts with the foundational principles of the healthcare system and is inconsistent with the Patient Rights Act. The amended Voluntary Assisted Dying Bill provides physicians with the options to both reject medically assisted dying applications and to employ safeguards to protect patients in transitional distress from premature death.